Wear properties of SiC particulate preplaced TIG melted surface layered duplex stainless steel - Maleque, Md. Abdul (2018)
The aim of this paper is to investigate the wear behavior of surface modified duplex stainless steel (DSS) with SiC particle preplacement using TIG torch technique under different process parameters. Surface modification is done using silicon carbide (SiC) particles on DSS substrate in order to form a new intermetallic surface layer. The effect of particle size, SiC preplacement, heat input and shielding gas flow rate on surface topography, hardness and wear rate are investigated. Observation of surface topography showed rippling marks which confirms that re-solidification process has been taken place during TIG melting. The highest hardness was obtained with the value of 1277 HV0.5kgf compared to substrate materials’ hardness value of 260 HV0.5kgf. The analyzed result showed that incorporation of SiC particles via TIG torch melting method increased the hardness of DSS by ~ five times. As the hardness increases, wear resistance of the surface layered DSS also increased accordingly.